Implementation of Digital Technology in Translation At the English Education Department IAIN Sultan Amai Gorontalo - Pakaya, Marina (Salus Publica: Journal of Community Service, 2024)
This study aims to explore the implementation of digital technology in Translation at English Education Department of IAIN Sultan Amai Gorontalo. Digital technology has brought significant changes in learning methods, especially in English language teaching. In this study, various digital devices and platforms, such as language learning apps, social networks, and other digital resources, were explored to improve students' English skills. This study was designed using a qualitative approach with observation, interviews, and document analysis to determine the effectiveness and challenges faced in this technology application. The results showed that using digital technology in translation learning can increase learning motivation, enrich learning materials, and provide interactive experiences that support the learning process. However, this study also revealed a number of obstacles, including limited infrastructure, lecturers’ and students’ abilities to adapt to technology, and the limited ability of lecturers in technology.  The recommendations of this study include the need for more in-depth training, improvement of technology facilities, and development of a digital-based curriculum to maximize the learning potential in the field of translation in the university environment